Nevoia de inovaţie în politicile de migraţie româneşti - Șerban, Monica (Calitatea Vieții, 2009)
From the social innovation perspective, the article addresses the issue of Romanian migration policies. I have tried to reason that, at the beginning of EU accession negotiations, Romania was caught in a contradictory situation, induced by the internal pressure for emigration and restrictive attitude of EU member states towards immigration. Between internal and external pressures, Romania implemented a set of measures with innovative character through which it tried to control, within the strict limits of intervention of a democratic emigration state, the departures that could lead to clandestine stayings abroad.